Creating the collective mind through virtual mirroring based learning. Issue 3 (11th April 2018) - Gloor, Peter; Fischbach, Kai; Gluesing, Julia; Riopelle, Ken; Schoder, Detlef
Abstract : Purpose: The purpose of this paper is to show that virtual mirroring-based learning allows members of an organization to see how they communicate with others in a visual way, by applying principles of "social quantum physics" (empathy, entanglement, reflect, reboot), to become better communicators and build a shared "DNA" within their organization. Design/methodology/approach: E-mail based social network analysis creates virtual maps of communication – social landscapes – of organizations, similar to Google Maps, which creates geographical maps of a person's surroundings. Findings: Applying virtual mirroring-based learning at various mulitnational firms has significantly increased their organizational efficiency and performance, for instance increasing customer satisfaction by 18 per cent in a large services organization, increasing retention, making sales forecasts, and improving call center employee satisfaction. Research limitations/implications: To address concerns of individual privacy, the guiding principle is to give individual information to the individual and provide aggregated anonymized information to management. Originality/value: Virtual mirroring-based learning offers a unique way of creating collective awareness within an organization by empowering the individual to take corrective action aligned with collective action, and improves their own communication behavior through analyzing and visualizing their e-mail archive in novel ways, while giving strategic insight to management and improving organizational culture.